A Cross Section Survey Assessment Study on the Knowledge and Practice of Periodic Medical Check up among the Saudi population - Sheriff Maqbul Muazzam; Dafallah Alghamdi Rawabi; Waleed Bakhsh Lama; Awad Almashjari Nadya; Hamid Alanazi Shamukh; Abdulqader bahshwan Amjad; Abdullatif Khan Aejaz; Shakeel Iqubal S.M.; Rahman Ikbal Abdul (Journal of New Developments in Chemistry, 2021)
In Saudi Arabia most of the individuals give very little attention to issues like health or no priority to medical checkup. This investigation was carried out to measure knowledge, practice of periodic medical checkup in Kingdom of Saudi Arabia people. A cross-sectional investigation was conducted among 1015 participants. A structured interviewer administered an online questionnaire were distribute by social media and whatsApp. We collected data and analyzed using SPSS version 21. Association between categorical variables were explored using bar chart and tables, Level of significance was set at 5%. The main age of the respondents was 21-30 years, 78.4% were females and 64.2% were married. About 42.1% have ever heard of periodic medical check-up , 57% of those who haven’t ever heard of periodic medical checkup and only 21.9% among those who had ever done it had frequent medical check-up and 78.1% didn’t do it. Attempt is required in ensuring that periodic medical check-up is urged. There is a need to study the factors associated with the uptake of medical check-up among the study population and effort should be made by health agencies to educate traders on the various types of medical check-up, their indications and benefits as well as its practice encouraged
Keywords: Awareness